The effectiveness of eye-closure in repeated interviews - Vredeveldt, Annelies (Legal and criminological psychology, 2014)
Purpose Closing the eyes during recall can help witnesses remember more about a witnessed event. This study examined the effectiveness of eye-closure in a repeated recall paradigm with immediate free recall followed 1 week later by both free and cued recall. We examined whether eye-closure was more or less effective during the second free-recall attempt compared with the first, whether eye-closure during the first recall attempt had an impact on subsequent free- and cued-recall performance, and whether eye-closure during the second free recall could facilitate the recall of new, previously unreported, information (reminiscence). Method Participants witnessed a videotaped event and participated in a first free-recall attempt (with eyes open or closed) a few minutes later. After a week, they provided another free recall, followed by a cued-recall interview (with eyes open or closed). Results Eye-closure during the first free-recall attempt had no significant effect on performance during any of the recall attempts. However, eye-closure during the second session increased the amount of correct visual information reported in that session by 36.7% in free recall and by 35.3% in cued recall, without harming testimonial accuracy. Crucially, eye-closure also facilitated the recall of new, previously unreported visual information. Conclusions The findings extend previous research in showing that the eye-closure instruction can still be effective when witnesses are interviewed repeatedly, and that it can facilitate the elicitation of new information. Thus, the eye-closure instruction constitutes a simple and time-efficient interview tool for police interviewers.